2020
DOI: 10.1002/smi.2964
|View full text |Cite
|
Sign up to set email alerts
|

Increases of negative affect following daily hassles are not moderated by neuroticism: An ecological momentary assessment study

Abstract: The occurrence of daily hassles is associated with increased subsequent levels of negative affect. Neuroticism has been found to exacerbate this effect. So far, most research used single-item measures for the assessment of daily hassles or relied on daily diary studies. This study aimed to examine the interrelations of daily hassles, negative affect reactivity, and neuroticism in daily life employing an extensive inventory of daily hassles. Seventy participants (18-30 years; M = 23.9 years, 59% female) complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
(137 reference statements)
0
8
2
1
Order By: Relevance
“…Thus, this circumstance may complicate the comparability of results across seemingly very similar studies. To illustrate, a recently published study found no evidence for neuroticism moderating the within-person link between negative affect and daily stressors (Mey et al, 2020). This contradicts the the findings reported in our study, as well as the majority of studies revealing an impact of neuroticism on stress reactivity following daily hassles (e.g., Bolger & Schilling, 1991;Marco & Suls, 1993;Mroczek & Almeida, 2004;Suls et al, 1998).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, this circumstance may complicate the comparability of results across seemingly very similar studies. To illustrate, a recently published study found no evidence for neuroticism moderating the within-person link between negative affect and daily stressors (Mey et al, 2020). This contradicts the the findings reported in our study, as well as the majority of studies revealing an impact of neuroticism on stress reactivity following daily hassles (e.g., Bolger & Schilling, 1991;Marco & Suls, 1993;Mroczek & Almeida, 2004;Suls et al, 1998).…”
Section: Discussioncontrasting
confidence: 99%
“…However, Mey et al. (2020) used a small sample ( N = 70), employed a brief measure of affect valence with two uncommonly used items (i.e., discontent, unwell), and had relatively long temporal periods covered by each prompt. Thus, it is possible that any number of these choices could have impacted their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst we include discussion of two broad trait dimensions, there is promise for understanding more specific traits using ecological frameworks, such as increasing interest in human social thermoregulation traits, where social affiliation is related to homeostatic needs of individuals (see IJzerman et al., 2015). Moreover, there is increasing interest in exploring the role of personality across environments with “ecological momentary assessment” tools (e.g., Mey et al., 2020; Wilson et al., 2017) and there is productive scope in considering ways in which traits in contexts could be understood as dynamic perception‐action processes.…”
Section: The Ecological Approachmentioning
confidence: 99%
“…In ihrer validierten Version erfasst das MIMIS 58 Stressoren des täglichen Lebens und ist für die digitale Erfassung sowohl am PC als auch mobil auf dem Smartphone validiert. In der Kombination mit Messungen des Affekts können hoch zeitlich aufgelöst die Effekte alltäglichen Stresses auf die psychische Verfassung gemessen werden [26].…”
Section: Definitionen Konzepte Und Operationalisierung Von Resilienzunclassified